Representasi Perempuan di Masjid - Nurhakki, Nurhakki; Haq, Islamul (Asosiasi Prodi Komunikasi dan Penyiaran Islam (Askopis), 2017)
When women are in the public space, the mosque becomes a choice of worship places either mahdoh or mahash mahhab. That is, the mosque must prepare facilities that are responsive to these needs such as separate ablution places, dressing rooms, special doors so that women do not violate the aurat (khillaqiyah) boundary while in the mosque. This case study research examines the representation of women in the Parepare City mosque. The results of this study indicate that the mosque facilities in Kota Parepare are not gender responsive because there is refraction on women's gender. The data of field observation with ablution category are: united, separate open, separate closed, then only 5% mosque which is friendly to woman with indicator set up facility of separate covered wudhu room. Refraction occurs because men are the dominant voice both in the structure of the field of idarah, imarah, and ri’ayah so that the voice of men becomes central in the communication process of mosque planning and development, the representation of women in the mosque is neglected and silent. Saat perempuan berada pada ruang publik, masjid menjadi pilihan tempat ibadah baik ibadah mahdoh maupun ghairu mahdoh. Artinya, masjid harus menyiapkan fasilitas yang responsif pada kebutuhan tersebut seperti tempat wudhu terpisah tertutup, ruang ganti, pintu khusus agar perempuan tidak melanggar batas aurat (khillaqiyah) saat berada di masjid. Penelitian studi kasus ini mengkaji tentang represenatsi perempuan di masjid Kota Parepare. Hasil penelitian ini menunjukkan bahwa fasilitas masjid di Kota Parepare tidak responsif gender karena terjadi pembiasan pada gender perempuan. Data observasi lapangan dengan kategori tempat wudhu yakni: menyatu, terpisah terbuka, terpisah tertutup, maka hanya 5 % masjid yang ramah terhadap perempuan dengan indikator menyiapkan fasilitas ruang wudhu terpisah tertutup. Pembiasan terjadi oleh karena laki-laki adalah dominan suara baik dalam struktur bidang idarah, imarah, dan ri’ayah sehingga suara laki-laki menjadi sentral dalam proses komunikasi perencanaan dan pengembangan masjid, representas perempuan di masjid terabaikan dan bungkam.